ОСВІТНЬО-КУЛЬТУРНЕ ВІДРОДЖЕННЯ УКРАЇНИ В ПЕРІОД ЦЕНТРАЛЬНОЇ РАДИ (за газетними джерелами 1917ñ1918 рр.) (Zaporizhzhia Historical Review, 2021)
In the article the author, basing on the vast press materials, investigates the history of public education development in Ukraine in the time of Central Rada (Council) period (1917ñ1918).